Terbanggi Besar - Pematang Panggang Toll Road Tariff Based On Ability to Pay and Willingness to Pay - Rosalita, Liza; Purba, Aleksander; Sulistiyorini, Rahayu (Universitas Lampung, 2019)
Transportation is a very important aspect to stimulate the economy, a region cannot be totally independent in meeting its own regional needs, so that the area needs other regions as a support where one of the connecting infrastructure is a toll road. The Terbanggi Besar - Pematang Panggang Toll Road is one of the 8 Trans Sumatra toll road projects that have entered the construction phase in 2017 which are planned to be operated in 2021. The tariff analysis carried out is based on the Ability to Pay (ATP) and Willigness to Pay (WTP) approach. The average ATP value obtained is Rp 131,638.00 / 100 km and the average WTP value obtained is Rp. 40,989.00 / 100 km. Respondent's ATP value > WTP value indicates that the ability to pay respondents is greater than willingness to pay because users have relatively high income but the utility of these services is relatively low. While the determination of ideal rates is based on the average value of ATP and WTP. Based on calculations, the price of the Terbanggi Besar - Pematang Panggang toll roads tariff is Rp. 86,314.00 / 100 km.